2010
DOI: 10.1149/1.3469570
|View full text |Cite
|
Sign up to set email alerts
|

Oscillations and Pattern Formation in a PEM Fuel Cell with Pt/Ru Anode Exposed to H[sub 2]/CO Mixtures

Abstract: In this work, the behavior of a polymer electrolyte membrane ͑PEM͒ fuel cell with a Pt/Ru anode exposed to H 2 /CO mixtures is investigated. A compact, isothermal one-dimensional model is derived to address the phenomena occurring at the along-thechannel direction. Besides material balances for the anode channel and electrode, the model considers charge balances for the membrane ͑Laplace equation͒ and both the anodic and cathodic double layers. The model predicts the formation of complex spatiotemporal pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 22 publications
5
34
1
1
Order By: Relevance
“…It can be seen that the differences between the Pd‐Pt/C and Pd/C systems studied herein, and their differences relative to the Pt‐Ru/C system, which is widely discussed in the literature, reflect different adsorption/oxidation kinetic constants of CO and of H 2 , in addition to the H 2 O dissociation on the catalyst surface for the formation of OH ad . As first proposed by Lopes et al., CO‐stripping voltammetry can be used to estimate the mean amplitude of oscillation.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…It can be seen that the differences between the Pd‐Pt/C and Pd/C systems studied herein, and their differences relative to the Pt‐Ru/C system, which is widely discussed in the literature, reflect different adsorption/oxidation kinetic constants of CO and of H 2 , in addition to the H 2 O dissociation on the catalyst surface for the formation of OH ad . As first proposed by Lopes et al., CO‐stripping voltammetry can be used to estimate the mean amplitude of oscillation.…”
Section: Resultssupporting
confidence: 90%
“…In contrast, for the system with a Pd‐Pt/C anode the dynamic begins as 2‐period. Hanke‐Rauschenback et al . addressed oscillations and pattern formation in PEMFCs with a PtRu anode fed with H 2 /CO by using a one‐dimensional isothermal model and found that if the system is limited by CO transport within the anodic chamber rather than being limited by CO adsorption, the system shows period‐doubling.…”
Section: Resultsmentioning
confidence: 79%
“…Each nucleation site can be seen as an oscillator; depending on the coupling between these oscillators, complex spatiotemporal patterns can form303132. If the oscillators are strongly coupled to each other, they oscillate synchronously; our model results in this scenario because of the periodic repetition of the unit cell.…”
Section: Model Developmentmentioning
confidence: 96%
“…The authors found that the spatially lumped model of Zhang and Datta (2002) is not able to reproduce the period 2 oscillations (Mota et al 2009 ) and suspected a spatiotemporal evolution of a CO carpet within the cell as a possible origin of the observed behavior (Mota et al 2010 ). Hanke -Rauschenbach et al (2010) extended the model of Zhang and Datta (2002) to a spatially one-dimensional formulation. The extended model mainly considers changes into the direction along the channel and predicts the formation of complex spatiotemporal patterns for a wide range of technical relevant operating conditions (Figure 12 ).…”
Section: Subsequent Studies -Spatiotemporalmentioning
confidence: 99%
“…In a subsequent study, Thomason et al (2004) brought the fi ndings of in context with methods to increase the CO tolerance of PEMFCs, such as air bleed (e.g., Gottesfeld and Pafford 1988 ), current pulsing (e.g., Carrette et al 2001 ), and Figure 12 Diagram taken from Hanke -Rauschenbach et al (2010) illustrating the behavior of the spatially distributed system for low feed fl ow rates: (A) temporal evolution of the cell voltage U cell ( t ); spatiotemporal evolution of the (B) anode double layer potential ∆ ϕ ( z , t ); (C) CO surface coverage θ CO (z, t ); (D) local anodic current density i a ( z , t ), and (E) CO mole fraction in the gas channel x CO (z, t ). Reproduced from Hanke -Rauschenbach et al (2010) by permission of ECS -The Electrochemical Society. the use of advanced electrocatalysts (e.g., Wee and Lee 2006 ).…”
Section: Technical Applicationsmentioning
confidence: 99%